2022
DOI: 10.1017/s0954579421001656
|View full text |Cite
|
Sign up to set email alerts
|

Within-dyad bidirectional relations among maternal depressive symptoms and child behavior problems from infancy through preschool

Abstract: Although dyadic theory focuses on the impact of a mother’s mental health on her own child and the impact of a child’s mental health on their own mother, commonly used statistical approaches are incapable of distinguishing the desired within-dyad processes from between-dyad effects. Using autoregressive latent trajectory modeling with structured residuals, the current study evaluated within-dyad, bidirectional associations between maternal depressive symptoms and child behavior problems from child age 1–4.5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Studies have also examined transactional influences between mothers and offspring, acknowledging that maternal moods and behavior can impact offspring, but that offspring can also affect their mothers (Sameroff, 2010). For instance, longitudinal studies have shown that while maternal depression and child behavioral difficulties (e.g., internalizing and externalizing behaviors) are associated during infancy and early childhood, these difficulties also predicted future symptoms of maternal depression (Baker et al, 2020;Curci et al, 2022;Roubinov et al, 2022). Despite the stresses imposed on parents and families by the pandemic, no studies have compared associations between PPD and infant temperament prior to and during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also examined transactional influences between mothers and offspring, acknowledging that maternal moods and behavior can impact offspring, but that offspring can also affect their mothers (Sameroff, 2010). For instance, longitudinal studies have shown that while maternal depression and child behavioral difficulties (e.g., internalizing and externalizing behaviors) are associated during infancy and early childhood, these difficulties also predicted future symptoms of maternal depression (Baker et al, 2020;Curci et al, 2022;Roubinov et al, 2022). Despite the stresses imposed on parents and families by the pandemic, no studies have compared associations between PPD and infant temperament prior to and during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In still another study on maternal depressive symptom effects on child behavior from infancy to preschool (N=322 low income Mexican-American mothers), the mothers reported depressive symptoms and child behavior problems from year one to 4.5 years [13]. Bi-directional associations were noted between the mothers' depressive symptoms and the children's behavior problems as early as one year, and those remained stable across the four-year period.…”
Section: Parental Risk Factorsmentioning
confidence: 89%
“…Nearly one in five mothers experience elevated depressive symptoms during the postpartum period (Gavin et al, 2005; O’Hara, 2009; Vesga-López et al, 2008). This high prevalence is of concern both because of the burden on mothers and the potential cascading effects of maternal depression on child outcomes (e.g., increased risk of behavior and self-regulation problems and psychopathology; Cents et al, 2013; Curci et al, 2022; S. H. Goodman et al, 2011).…”
Section: Timing Of Maternal Depressive Symptomsmentioning
confidence: 99%